Images of the Toronto Provincial Asylum, 1846-1890 - Flis, Nathan (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2009)
AbstractBuilt in 1850, the Toronto Provincial Asylum was once the largest mental hospitals in Canada. The main building was demolished in 1975, and the property is now home to the Queen Street branch of the Centre for Addiction and Mental Health. Although there are remnants of the nineteenth-century institution, including most of the perimeter wall, the only lasting visual reminder of the property as a whole is a small group of images. By the last quarter of the nineteenth century, perhaps in order to ease public concern over the increasingly custodial function of the institution, Victorian media sources repeatedly presented an unchanging or immutable depiction of the Toronto Asylum. Drawing upon the architectural concept drawings of the 1840s, which contained an ideal vision for the building, pictures from the 1870s, 80s and 90s depict the asylum as the new, clean, and proud-looking structure it was when it opened. Arguably, these images are what the Victorian public wanted to see: they preserved the early-century optimism that such institutions would yield high cure rates and they supported the view that the care of the mentally ill belonged in the hands of the medical profession.